Role of Impoundments Created by Low-Head Dams in Affecting Fish Assemblages in Subtropical Headwater Streams in China - Li, Qiang; Li, Xiang; Fu, Haixia; Tan, Kai; Ge, Yihao; Chu, Ling; Zhang, Chen; Yan, Yunzhi (Frontiers in Ecology and Evolution, 2022)
Low-head dams are ubiquitous human disturbances that degrade aquatic ecosystem function worldwide. The localized effects of low-head dams have been relatively well documented; however, most previous studies have ignored the concealed process caused by native-invasive species. Based on fish assemblage data from the first-order streams of four basins in the Wannan Mountains, we used a qualitative approach to assess the effects of low-head dams on fish assemblages by distinguishing between native and native-invasive species using incidence- and abundance-based data, respectively. Low-head dams significantly decreased native fish alpha diversity while favoring native-invasive fish. The opposite pattern between the two fish types partly masked changes in the entire fish assemblage. Meanwhile, the establishment of widespread native-invasive species and the loss of native species driven by low-head dams influenced the interaction network structure. The degree to which local fish assemblages were altered by low-head dams (i.e., beta diversity [β-diversity]) was significantly higher for abundance-based approaches than for incidence-based ones, suggesting that the latter underestimated the effects of low-head dams. Furthermore, the site occupancies of native and native invasive species were positively correlated with the species contribution to β-diversity (SCBD), while a hump-shaped relationship for native species was observed only in incidence-based cases. Our results suggest that understanding which species contribute most to SCBD will contribute to the development of effective conservation strategies aimed at mitigating the ecological consequences of low-head dams.